Mispronunciation of high front and low Hausa vowels among the Yorùbá speakers - Maikanti, Sale; Burkhardt, Jurgen Martin; Yong, Mei Fung; Husain, Salina; Oludare, Olúwadọrọ̀ Jacob (Secholian Publication, 2021)
Pronunciation in second language learning is sometimes challenging, especially the vowels. Vowels such as [i] and [a] are found both in Hausa and Yorùbá but [i:] and [a:] are peculiar to Hausa alone. While Hausa has short and long vowels, Yorùbá has only oral and nasal vowels in their vowel inventories. Such phonemic differences constitute learning challenges, especially for the Yorùbá native speakers. This is a cross-sectional study design using mixed methods to examines the production of high front vowels: [i], and [i:], as well as low: [a], and [a:] Hausa vowels by the Yorùbá speakers to identify which group perform better between group 1 (Yorùbá native speakers who learned Hausa in the secondary school before going to the college of education), and group 2 (Yorùbá native speakers who learned Hausa informally before going to the college of education). The study also seeks to find out vowel substitutions that occur in the pronunciation tasks using 80 participants from 18 years old and above from the College of Education system in Nigeria who were selected based on purposive sampling. The findings were discussed in line with Flege & Bohn’s (2020) ‘Revised Speech Learning Model’. 8 stimuli were audio-recorded, transcribed, and rated by two independent raters, in addition to participant observation techniques adapted. The results of the Mann-Whitney test revealed that group 2 performed better than group 1. The study discovered also that the short [a] in the first and second syllables had the highest frequency of substitution compared to [i], [i:] and [a:] vowels. Such problems have pedagogical implications for learning Hausa as a second language.